MARIFAT WING – LITERATURE (American Journal of Pedagogical and Educational Research, 2022)
This article is devoted to the life and work of Abdulhamid Sulaiman son of Cholpon, the representative of the Jadid movement, poet, writer, translator, dramatist, great writer, and how important literature is for our society through the work of Jadid.